The adjacency dimension of some path related trees - Elham Hardany; Ali Behtoei (Journal of Mahani Mathematical Research)
‎Since the problem of computing the adjacency dimension of a graph is NP-hard‎, ‎finding the adjacency dimension of special classes of graphs or obtaining good bounds on this invariant is valuable‎. ‎In this paper we determine the properties of each adjacency resolving set of paths. ‎Then, ‎by ‎using ‎these ‎properties,‎ we determine the adjacency dimension of broom and double broom graphs‎.